“Estudio tecnico para la elaboracion de conseva de pescado ahumado de la especie “PACO” piaractus brachypomus en salsa de tomate” - Silva Torres, Mariliquiz (2008)
The present investigation work you carries out in the city of !quitos, in the facilities o, f the CRI - lnstitute of lnvestigation of the Peruvian Amazonía, of the National University of the Peruvian Amazonia {Ability of Engineering in Alimentary Industries and of Biological Sciences), of the Company Nauta S.A whose main objective was to establish the parameters to obtain a product with characteristic organolépticas, physical-chemical, microbiológicas, and nutritious for the consumption human. During the development of this work 90 specimens were used and they have carried out a series of experiments, to evaluate and to obtain the good parameters of prosecution, being achieved the following process conditions: Matter Prevails; Lavado/Pesado; Desescamado/Fileteado/Eviscerado; Laundry I Bled with water clorada and brine to 2%; Ensalmuerado for 30 min al 10% or to 20 % for 15 min; mellow with vinegar ,sal and ajinomoto; drained; smoked by 2.5 hours to staggered temperature from 50 to 90 ºC; cooled by 12 hour; cut in small fillets; packed I Weighed in cans of % he/she liberates; Filled with tomato sauce like 1 liquidate of government; evacuated at 95ºC by 8 minutes; sealed I laundry; thermal Treatment I Cooled to 120.4 ºC po 60 minutes and 0.77 kg/cm2; cooled by 10 minutes until the ambient temperature; Storage for 60 days to ambient temperature. The final product has a composition chemical proximal following average: Humidity: 70.00 %; protein: 20.10 %; fat: 5.00 %; ash: 2.00 %; carbohydrate: 2.90 % y Nacl: O. 70 %.